Edukasi Karakter dan Akhlak Mulia Anak bagi Guru PAUD dan TPQ di Kecamatan Mojoagung - Qomarijah, Oemi Noer; Darihastining, Susi; Dinarti, Siti (Jurnal Pengabdian Masyarakat, 2025)
Character education and good morals are the main foundations in shaping a superior generation that is not only intellectually intelligent, but also ethical, moral, and socially minded. Early Childhood Education (PAUD) and Al-Qur'an Education Parks (TPQ) are strategic environments for instilling these values from an early age. However, many teachers in PAUD and TPQ institutions still lack adequate understanding and pedagogical skills in integrating character values into the learning process. This community service activity aims to enhance the capacity of PAUD and TPQ teachers in Mojoagung Sub-district, Jombang, through training in character education and noble moral values for children. The implementation methods include participatory training with an interactive approach, group discussions, simulations, case studies, and post-training online mentoring. A total of 40 participants enthusiastically joined the activity. Data was collected through observation, feedback questionnaires, and unstructured interviews. The training results demonstrated an increase in participants' understanding of character education concepts and practices, as well as their enthusiasm to implement them in educational activities. Challenges such as time constraints and diverse participant backgrounds were successfully addressed through flexible approaches and intensive communication. This activity demonstrated that character education training can make a significant contribution to strengthening teachers' understanding of their role as agents in shaping the next generation into individuals of character and noble ethics.